“La cultura tributaria y su influencia en el cumplimiento de las obligaciones tributarias de los comerciantes del distrito de Morales. Año 2015” - Arévalo Revilla, Henry (2016)
Our research did in order to determine how the tax culture affects compliance with the tax obligations of traders located in the jurisdiction of the District of Morales, belonging to the province of San Martin, San Martin Region; the same according to the intended purpose is an applied research, for which we use the survey as a technique to collect required information. The theoretical part is a compilation of physical and virtual information we extracted the proper and specific information related to the object of our work, among these we get theses related, books, internet, among others; data that contributed to the foundation of our work. The universe of this study consisted of the population of the District of Morales, belonging to the province of San Martin; our population was framed by all commercial establishments registered in the register of licenses of the District Municipality of Morales, 2015, consisting of a total of 1118 licenses. The information gained through our 266 survey, consisting of 10 questions each, were tabulated and then processed graphically, allowing the interpretation of results, the discussion thereof, and the conclusions and recommendations.